2010
DOI: 10.1007/978-90-481-9485-8_28
|View full text |Cite
|
Sign up to set email alerts
|

Advocacy Groups and Their Role in Rare Diseases Research

Abstract: One of the remarkable and unique aspects of the recent history of rare disease research has been the evolving role of patient advocacy groups and the collaborative partnership that exists among such groups and the scientists who study rare diseases, as well as the government officials charged with overseeing medical research and regulatory processes. This collaboration, which in many respects developed out of necessity on all sides, is unparalleled in other areas of medical research and product development. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 1 publication
0
45
0
Order By: Relevance
“…Respondents who indicated that their organization had not been previously involved with research were not asked this series of questions. Information to give subjects 45 (38) 29 (24) 20 (17) 6 (5) 19 (16) How to recruit subjects 40 (34) 29 (24) 21 (18) 12 (10) 17 (14) Topics to study 40 (34) 27 (23) 26 (22) 13 (11) 13 (11) The goals of the study 35 (29) 37 (31) 26 (22) 6 (5) 15 (13) How a study is designed 24 (20) 16 (13) 40 (34) 16 (13) 23 (19) Values are expressed as N (%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents who indicated that their organization had not been previously involved with research were not asked this series of questions. Information to give subjects 45 (38) 29 (24) 20 (17) 6 (5) 19 (16) How to recruit subjects 40 (34) 29 (24) 21 (18) 12 (10) 17 (14) Topics to study 40 (34) 27 (23) 26 (22) 13 (11) 13 (11) The goals of the study 35 (29) 37 (31) 26 (22) 6 (5) 15 (13) How a study is designed 24 (20) 16 (13) 40 (34) 16 (13) 23 (19) Values are expressed as N (%).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Many disease advocacy organizations (DAOs), which enable individuals with a shared interest to pool their collective resources and shared knowledge of a medical condition, work closely with clinicians and scientists, particularly in the United States. [17][18][19] DAOs are becoming more common in other countries as well, including the developing world. 20,21 Although DAOs have traditionally been associated with patient education and support, recent evidence suggests that their involvement in clinical research may be expanding.…”
Section: Introductionmentioning
confidence: 99%
“…Over the course of the past 30 years, patient advocacy groups have been instrumental in raising awareness, advancing the science, and ensuring that patients have access to the appropriate health care and treatments they need. 9 The most successful groups have approached this through collaboration among key stakeholders in government, academia, and health care. Autism Speaks has been successful in advancing science and clinical care by influencing policy makers to recognize the complex challenges faced by their constituents and sharing their sense of urgency and purpose to ensure that policies do not stand in the way of research and treatment.…”
mentioning
confidence: 99%
“…Most of these disorders fit into the 'rare disease' category. [6][7][8][9] Often an organisation will bring together a surprisingly large number of affected individuals who are willing to take part in research projects. The advocacy can be for research regarding natural history information, for management and care, or for therapy.…”
Section: Parent Support Group Activitiesmentioning
confidence: 99%